Ezekiel 18 and Human rights - H.F. van Rooy (Verbum et Ecclesia, 2000)
In South Africa the debate on Human Rights gained new impetus after the implementation of the interim constitution in 1994, followed by the new constitution in 1996, containing a charter of fundamental Human Rights. The question to be answered by this paper is whether Ezekiel 18 can contribute to this debate. This paper firstly discusses the question whether the Old Testament can be used in the debate on Human Rights. This is followed by a discussion of Ezekiel 18, with emphasis on the transgressions listed in this chapter in their Israelite context. Many of these injunctions are related to the laws of Deuteronomy, the Book of the Covenant and the Holiness Code. These injunctions are studied against the background of Israelite law in general and the three codes mentioned above in particular. Finally, the implications of Ezekiel 18 for the issue of Human Rights are discussed. The violation of rights of people guaranteed by divine law is seen as one of the major causes of divine punishment. God's law was meant to create a society found on justice. An unjust society is in contradiction to the will of God, according to Ezekiel 18. The implications of this view for the debate on Human Rights in South Africa need to be taken into consideration.